2023
DOI: 10.3389/fmicb.2022.985789
|View full text |Cite
|
Sign up to set email alerts
|

Phenylalanine-arginine β-naphthylamide could enhance neomycin-sensitivity on Riemerella anatipestifer in vitro and in vivo

Abstract: Riemerella anatipestifer is an important duck pathogen responsible for septicemia and infectious serositis, which has caused great economic losses to the duck industry. Phenylalanine-arginine β-naphthylamide (PAβN) is an efflux pump inhibitor, which mainly reduces the efflux effect by competing with antibiotics for efflux pump channels. Here, we found that R. anatipestifer strain GD2019 showed resistances to gentamicin, amikacin, kanamycin, and neomycin. Notably, PAβN could significantly reduce the Minimal inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 27 publications
0
1
0
Order By: Relevance
“…Only three references have been identified, indicating the involvement of specific genes in CPS biosynthesis in R. anatipestifer . These genes include a wza ‐like gene (the B739_1124 gene) of RA‐CH‐1 (corresponding to the GE296_RS03840 gene of RA‐LZ01), the M949_RS00050 gene of the CH3 strain and the G148_RS04320 gene (corresponding to the GE296_RS03845 gene) of CH‐2 6–8 . The CPS synthesis in R. anatipestifer involves multiple genes, as predicted in Figure 1.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…Only three references have been identified, indicating the involvement of specific genes in CPS biosynthesis in R. anatipestifer . These genes include a wza ‐like gene (the B739_1124 gene) of RA‐CH‐1 (corresponding to the GE296_RS03840 gene of RA‐LZ01), the M949_RS00050 gene of the CH3 strain and the G148_RS04320 gene (corresponding to the GE296_RS03845 gene) of CH‐2 6–8 . The CPS synthesis in R. anatipestifer involves multiple genes, as predicted in Figure 1.…”
Section: Discussionmentioning
confidence: 86%
“…R. anatipestifer is known to produce capsules, but the understanding of its capsular biosynthesis is limited. Previous studies have reported the presence of certain genes involved in capsule biosynthesis, such as wza ‐like, M949_RS00050 , and G148_RS04320 genes 6–8 . However, the complete mechanism of capsular biosynthesis in R. anatipestifer remains to be fully understood, as it can contribute to understanding the pathogenicity of the bacterium and provide targets for prevention and treatment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent study, up to 40 µg/g of PAβN combined with neomycin were injected intramuscularly into ducks infected with Riemerella anatipestifer. Treatment with PAβN coupled with neomycin significantly increased the survival rate and reduced the bacterial load and pathological changes in the heart, liver, and brain of treated animals [38]. Indeed, there is a need for more studies to confirm the safety and efficacy of PAβN in vivo before employing it for therapeutic purposes.…”
Section: Discussionmentioning
confidence: 99%
“…While a full literature review of its use is beyond the scope of this report, we would like to highlight PAβN's recent use cases where it has been employed to inhibit efflux while other disease relevant parameters are investigated including virulence phenotypes, [16][17][18] biofilm formation and disruption, [19] the development of antibiotic resistance, [20][21][22][23] and quorum sensing; [24] it is also used as a standard for benchmarking newly developed EPIs. [25][26][27] Further, it is commonly used during the development process of new antibiotics; [28][29][30][31][32][33] indeed, our laboratory's interest in PAβN originated during our investigations of antibacterial compounds [34] and natural products [35] that lacked activity against P. aeruginosa. Additional studies show that nonspecific membrane permeabilization may be another pathway by which PAβN potentiates antibiotics, independent of their efflux inhibition, further lending credibility to its broad application as a tool compound.…”
Section: Introductionmentioning
confidence: 99%